The Effect of Plastic Cover on Regulation of Vital Signs in Preterm Infants: A Randomized Cross-over Clinical Trial - Leila Valizadeh; Majid Mahallei; Abdolrasoul Safaiyan; Fatemeh Ghorbani; Maryam Peyghami (Mashhad University of Medical Sciences, 2017)
Background: Considering the susceptibility of preterm infants to disturbances of vital signs, this study was conducted to investigate the effects of using plastic covers on regulation of vital signs in preterm neonates.Methods: This randomized, cross-over, clinical trial was carried out on 80 preterm infants admitted to neonatal intensive care unit (NICU) of Taleghani Hospital, Tabriz, Iran. The study was conducted in two days (on the second and third days of the infants' life). In group 1, plastic cover was used during the first day followed by the use of blanket on the second day, while the order was reversed in group 2. Digital thermometer was used to measure the infants' axillary temperature. Heart rate and oxygen saturation were measured through monitoring. To analyze the data, descriptive (Mean and SE, 95%CI) and inferential statistics (repeated measurement and ANCOVA tests) were used in SPSS version 13 and MiniTab software.Results: Fourteen infants who were covered with blanket were found to suffer from hypothermia, while no infant with a plastic cover encountered this problem. The percentage of arterial blood oxygen saturation in the group with plastic covers was higher, and as a result, the infants received less oxygen supplements. However, no statistically significant differences were observed in heart rate between the groups.Conclusion: Use of plastic cover during NICU stay prevented hypothermia in premature infants, with the arterial blood oxygen saturation being within the normal limits. Yet, it did not seem to have a significant effect on other vital signs.